PENGARUH INFLASI, NILAI TUKAR DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM PADA SUB SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Deni Permana; Adun Rahman; Ujang Hasan Mustopa (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
The problems discussed in this research are 1) How are inflation, exchange rates, interest rates and share prices in the banking sub-sector listed on the Indonesian Stock Exchange. 2) What is the influence of inflation, exchange rates, interest rates partially on share prices in the banking sub-sector listed on the Indonesia Stock Exchange. 3) How is the influence of inflation, exchange rates and interest rates simultaneously on share prices in the banking sub-sector listed listed on the Indonesian Stock Exchange. The research results show that inflation financing, exchange rates, interest rates together have a significant positive effect on share prices in the banking sub-sector listed on the Indonesia Stock Exchange (BEI) for the 2008-2022 period.